Dopamine systems and biological rhythms: Let’s get a move on - Tang, Qijun; Assali, Dina R.; Güler, Ali D.; Steele, Andrew D. (Frontiers in Integrative Neuroscience, 2022)
How dopamine signaling regulates biological rhythms is an area of emerging interest. Here we review experiments focused on delineating dopamine signaling in the suprachiasmatic nucleus, nucleus accumbens, and dorsal striatum to mediate a range of biological rhythms including photoentrainment, activity cycles, out-of-phase eating of palatable food, diet-induced obesity, and food anticipatory activity. Enthusiasm for causal roles for dopamine in the regulation of circadian rhythms, particularly those associated with food and other rewarding events, is warranted. However, determining that there is rhythmic gene expression in dopamine neurons and target structures does not mean that they are bona fide circadian pacemakers. Given that dopamine has such a profound role in promoting voluntary movements, interpretation of circadian phenotypes associated with locomotor activity are nuanced. Here we review our current understanding of dopamine signaling in relation to biological rhythms and suggest future experiments that are aimed at teasing apart the role(s) of dopamine subpopulations and dopamine receptor expressing neurons in causally mediating biological rhythms, particularly in relation to feeding, reward, and activity.